2016
DOI: 10.1002/chem.201505003
|View full text |Cite
|
Sign up to set email alerts
|

Gas‐Phase Studies of Formamidopyrimidine Glycosylase (Fpg) Substrates

Abstract: Gas-phase thermochemical properties (tautomerism, acidity, and proton affinity) have been measured and calculated for a series of nucleobase derivatives that have not heretofore been examined under vacuum. The studied species are substrates for the enzyme formamidopyrimidine glycosylase (Fpg), which cleaves damaged nucleobases from DNA. The gas-phase results are compared and contrasted to solution-phase data, to afford insight into the Fpg mechanism. Calculations are also used to probe the energetics of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
(158 reference statements)
2
12
0
Order By: Relevance
“…As we noted earlier, in our experience, B3LYP/6‐31+G(d) yields accurate values for thermochemical properties of nucleobases. [ 25–36 ] For the purines studied herein, the calculated and experimental values in Table 3 are in agreement, within the experimental error, indicating that B3LYP/6‐31+G(d) appears to provide fairly accurate predictions for the thermochemical values. One exception is Apn PA, which we will discuss later in this section.…”
Section: Discussionsupporting
confidence: 68%
“…As we noted earlier, in our experience, B3LYP/6‐31+G(d) yields accurate values for thermochemical properties of nucleobases. [ 25–36 ] For the purines studied herein, the calculated and experimental values in Table 3 are in agreement, within the experimental error, indicating that B3LYP/6‐31+G(d) appears to provide fairly accurate predictions for the thermochemical values. One exception is Apn PA, which we will discuss later in this section.…”
Section: Discussionsupporting
confidence: 68%
“…Because the canonical tautomer is the most stable by about 10 kcal mol −1 for all four halouracils, we can assume that under our gas-phase conditions, the canonical structure is most likely the sole tautomer that is present. [3][4][5][6][7][8][9][10][11]15,18 Experimentally, there has been one prior measurement of 5-fluorouracil acidity by Chen and Chen (329 ± 4 kcal mol −1 ), which is consistent with our results. 32 Initially, we calculated 5FU, 5ClU, and 5BrU properties using B3LYP/ 6-31+G(d).…”
Section: ■ Discussionsupporting
confidence: 90%
“…In our prior work with both normal and damaged nucleobases, we have found that B3LYP/6-31+G­(d) computational acidity and PA values generally compare quite favorably to experimental values. ,, However, the 6-31+G­(d) basis set does not accommodate iodine, so we utilized the effective core potential def2-TZVP basis set of Ahlrichs and co-workers for the 5-halouracil calculations Figure shows the seven most stable calculated tautomers of 5FU ( 1 ); we show all tautomers that are within 15 kcal mol –1 of the canonical tautomer, 1a , as well as the acidity and PA of all the sites of all the tautomers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations